Interaction of Artificial Intelligence (AI) with Internet of Things (IoT) Technologies - Mammedova, A.M.; Zhilkishbaeva, G.S.; Mammedova, A.N. (Herald of Azerbaijan Engineering Academy, 2025)
Over the past decades, technologies, including the Internet of Things (IoT) and Artificial Intelligence (AI), have been rapidly evolving, significantly impacting various aspects of life. This article examines the interconnection between these technologies and analyzes how their integration accelerates the development of smart systems, enhances their efficiency, and addresses complex challenges. Additionally, it explores key trends, challenges, and prospects of IoT and AI integration, as well as their impact on different industries.